ANÁLISE DE INDICADORES DO PREVINE BRASIL - CAVALCANTI, Marcos Ronad Mota (2024)
This study aimed to analyze the temporal and spatial trends of health indicators under the Previne Brasil program between 2018 and 2021, as well as evaluate the impact of federal financial transfers for Primary Health Care (PHC) in Brazilian capitals. The research is structured into two articles. The first, titled "Is it possible to talk about improved access to prenatal care after Previne Brasil?", explores the historical context of PHC in Brazil, focusing on correlations between the Synthetic Final Index (SFI), Family Health Strategy (FHS) coverage, and the Human Development Index (HDI), with an emphasis on their influence on prenatal care indicators. This article aims to identify the behavior of Previne Brasil indicators from 2019 to 2022 and estimate the factors influencing these metrics. The second article, "Financing Primary Health Care in Brazil: analysis of federal transfers to Brazilian capitals from 2018 to 2022," compares financial transfers before and after the implementation of Previne Brasil, based on the premise that increased PHC coverage should correlate with proportional growth in investment and service offerings. The methodology included the calculation of the budgeted and received variation coefficient and its representation in line graphs. The results indicate a general improvement in health indicators over the studied period, despite the potential negative impact of the COVID-19 pandemic in 2020. Significant discrepancies were also observed in financial transfers among capitals, with some receiving amounts above the budgeted figures and others below. The study concludes that while Previne Brasil holds potential for improving access and quality in PHC services, a longer implementation period and consideration of contextual factors are necessary for a more conclusive evaluation. The research emphasizes the importance of a regionalized approach to resource allocation to ensure equity and efficiency in PHC financing.